2010
DOI: 10.1074/jbc.m110.151407
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Compensation Restores Trafficking of the Autosomal Recessive Retinitis Pigmentosa E150K Opsin Mutant to the Plasma Membrane

Abstract: Rhodopsin is the rod photoreceptor G protein-coupled receptor responsible for capturing light. Mutations in the gene encoding this protein can lead to a blinding disease called retinitis pigmentosa, which is inherited frequently in an autosomal dominant manner. The E150K opsin mutant associated with rarely occurring autosomal recessive retinitis pigmentosa localizes to trans-Golgi network membranes rather than to plasma membranes of rod photoreceptor cells. We investigated the molecular mechanisms underlying o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Previous studies in cell culture systems showed that the E150K mutation caused accumulation of positive charges on the cytoplasmic surface of rhodopsin (17,18). Here, we demonstrate that mouse rods expressing E150K rhodopsin undergo severe and rapid retinal degeneration.…”
Section: Figurementioning
confidence: 53%
See 2 more Smart Citations
“…Previous studies in cell culture systems showed that the E150K mutation caused accumulation of positive charges on the cytoplasmic surface of rhodopsin (17,18). Here, we demonstrate that mouse rods expressing E150K rhodopsin undergo severe and rapid retinal degeneration.…”
Section: Figurementioning
confidence: 53%
“…Most of these mutations cause adRP, accounting for 30%-40% of the total RP cases, whereas only a few, including severe truncation of the opsin gene (14), are inherited in an autosomal recessive pattern. The c.448G>A (p.E150K) mutation in patients was the first reported missense mutation in the opsin gene associated with arRP (15,16), and the resulting mutant protein has since been characterized in vitro by biochemical methods (17,18). Another mutation that causes arRP, G284S, is listed in RetNet, but without further biochemical characterization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified cellular distribution of GPCR mutants is a well documented phenomenon, which may occur naturally, sometimes causing pathologic conditions (Pulagam and Palczewski, 2010), or in site-directed mutagenesis (Milligan, 2009). We return to this issue under Discussion, whereas the rest of this work focuses on mutants that localize at the plasma membrane: W175A, R176K, Y198F, R151K/R152K, L159A/ L166A, and R176K/Y198F.…”
Section: Resultsmentioning
confidence: 99%
“…Both hydrophobic and non-polar TM1 0.0002 (C) T62 H-bond between TM1 and TM2 [ 73 ] Y146C rs200099863 Conserved in all species Both polar and similar hydrophobicity TM3 0.0002 (G) E113 Schiff Base Counterion [ 49 ] R168C b rs143641898 Conserved in all species Positive charge to polar. Increased hydrophobicity TM3 / IL2 0.0005 (T) R135 c Conserved DRY motif [ 47 ] S183P rs151123640 Conserved in most species (T in Amphioxus) Polar to non-polar IL2 0.0002 (C) E150 c Required for normal membrane trafficking [ 74 ] R186H b rs141089672 Conserved in most species (K in Chicken and Zebrafish) Both positive charge, increase in hydrophobicity IL2 0.0005 (A) Not conserved G208S rs549998450 Conserved in all species Non-polar to polar. Introduce large side chain TM4 EL2 0.0004 (A) G174 c Unknown V213M rs202171086 Conserved in Opn4M, l/V in Opn4X Both hydrophobic and non polar EL2 0.0002 (A) I179 Unknown ...…”
Section: Resultsmentioning
confidence: 99%